Application of Hybrid Nanocomposites to Enhance Extraction and Chromatographic Analysis of Antihistamines in Food and Water Samples - Sunaid, Hayder Kadhim (University of Thi-Qar Journal, 2026)
A novel analytical approach was developed for the extraction and quantification of antihistamines, clemastine and cyproheptadine, in various food and water matrices using a hybrid nanocomposite, APTES-GO@MIL-101(Cr), in combination with ultrasound-assisted dispersive micro solid-phase extraction (D-?SPE) and HPLC-UV detection. The hybrid nanocomposite was synthesized through functionalization of graphene oxide with 3-aminopropyltriethoxysilane (APTES) followed by incorporation of MIL-101(Cr), and its structural and morphological features were confirmed using FT-IR, SEM, and EDX analyses. Key factors influencing extraction efficiency, including desorption solvent type and volume, ultrasonication time, sample pH, salt concentration, extraction time, and adsorbent dosage, were systematically optimized. Under the optimized conditions, the method exhibited excellent linearity over the range of 0.1–20 ng/mL for both analytes with correlation coefficients (r²) exceeding 0.999. The limits of detection (LOD) and quantification (LOQ) were 0.04 and 0.134 ng/mL for clemastine, and 0.045 and 0.15 ng/mL for cyproheptadine, respectively. The method also demonstrated high precision with intra- and inter-day relative standard deviations (RSDs) below 5%, and the adsorbent could be reused for at least 30 extraction cycles with minimal loss in performance. Application to real samples, including milk, egg yolk, chicken meat, mutton, and water, resulted in recoveries ranging from 92% to 102%, confirming the robustness and reliability of the approach. This strategy provides a simple, rapid, sensitive, and environmentally friendly method for monitoring trace levels of antihistamines in complex food and environmental matrices